SOCIOLINGUISTIC ASPECTS OF THE STUDY OF PECULIARITIES OF RADIO COMMUNICATION - Pazyura, Nataliya (Proceedings of National Aviation University (archive), 2016)
Purpose. Flight safety has always been in the center of attention of scientists and practitioners in aviation. That is why in the end of the last century the ICAO assembly recognized inadequate English proficiency among flight crews and controllers as a contributing factor in aviation accidents. It also directed the ICAO’s Air Navigation Commission (ANC) to strengthen the provisions for the use of English in aeronautical radiotelephony (air traffic communications) in Annex 1 - Personnel Licensing and Annex 10 – Aeronautical Telecommunications. Results. The article is devoted to the study of peculiarities of communication in aviation – radio communication between an air traffic controller and pilot, which is very important for promotion of flight safety. The author pays special attention to the study of social factors influencing the choice of certain lexical units and functional styles. Methods. For our research we used scientific general methods which are main ways of studying scientific sources, and comparative-historical method for synchronic comparison of event in the same region. Discussion. The factors that explain such linguistic choice during communication have been characterized. Similar and different features of professional radio communication and usual every day communication have been revealed. Some examples are given and explained according to specific professional activity.